E-Policing dan Implikasi Kebijakan Pengelolaan Keamanan Publik - Lalu Guruh Prawira Negara (Syntax Corporation Indonesia, 2024)
This study aims to analyze the implementation of E-Policing in the management of street crime reports in Depok City in the period May to August 2024. By utilizing information and communication technology, E-Policing functions to increase efficiency, speed, and accuracy in crime reporting and handling. The method used in this study is a combination of quantitative surveys and qualitative interviews from the people of Depok City. The results of the study show that the implementation of the